La co-construction des savoirs dans un territoire : une démarche de recherche-action à Clermont-Ferrand - Lamia Badra; Éric Dacheux (Communication)
Through action research on the co-construction of local knowledge, we seek to understand how the cross-fertilization of knowledge between local actors may or may not lead to open and fruitful exchanges on ongoing projects. We begin by examining the meaning given to the concepts of local, co-construction, and cross-fertilization of knowledge. We then look at an action research project carried out in Clermont-Ferrand, France, involving a wide range of local actors to see whether or not it is possible to agree on the objectives of collaboration locally and how the actors share their knowledge. We see how these actors have compared their views on the collaborative projects carried out locally and present the results of exploratory surveys demonstrating a shared desire to continue the discussions in order to feel involved in the co-construction process. Lastly, we consider new perspectives for the evolution of this experience.